Genetic Implications in High-Risk Pregnancy and Its Outcome: A 2-Year Study - Afifi, Hanan H.; Gaber, Khaled R.; Thomas, Manal M.; Taher, Mohamed B.; Tosson, Angie M.S. (American Journal of Perinatology, 2021)
Objective The aim of this study is to evaluate high-risk pregnant females' offspring as regard the presence of any medical condition, hereditary disorder, or major anomaly as well as to document parental sociodemographic characteristics and compliance with follow-up schedules of fetal medicine and clinical genetic clinics.Study Design This prospective 2-year cohort study of neonates and infants reported the referral indications, investigations, and diagnoses obtained through prenatal and postnatal examinations. It also reported their parental follow-up vigilance.Results Of the 811 infants of high risk females referred 460 (56.7%) came for assessment. Mean parental consanguinity and endogamy were 67 and 71.3%, respectively. All pregnant mothers underwent first-trimester biochemical testing (plasma protein-A, α-fetoprotein [AFP], human chorionic gonadotropin [hCG]) and serial ultrasound examinations. Seventy mothers needed second-trimester biochemical testing (AFP, hCG, and estriol). Sixty-two mothers underwent amniocentesis where G-banding karyotype, fluorescence in situ hybridization and targeted molecular testing for the specific gene mutation of single gene disorders were conducted according to suspected disorders. High quality fetal ultrasound was performed when brain malformations were suspected, while 16 fetuses required brain MRI examination. Mean age of newborns at first examination was 26.5 days. They were grouped according to the maternal indication for referral. Upon examination, 18 neonates had confirmed congenital malformations/genetic disorders. Five of them were diagnosed prenatally. In four other fetuses with single gene disorder, the molecular diagnosis of their affected siblings was not established prior to this pregnancy; thus, prenatal diagnosis was not possible. The remaining nine cases were diagnosed postnatally.Conclusion Parental consanguinity and endogamy were increased among high-risk pregnancies. Public awareness about potential adverse effects of consanguineous marriages and the importance of genetic testing are imperative. A structured multidisciplinary team of specialists in fetal medicine, clinical genetics, and neonatology provides good genetic services. Expansion and financial support of these services are urgently required.Key Points
Keywords: neonates and infants; genetic disorders; high-risk pregnancy; prenatal testing; multidisciplinary approach; parental consanguinity